Planning Science Lessons Using 5E Instructional Model - Zengin, О.; Kalkabekova, Zh.S.; Ganyukova, А.А. (Ye.A.Buketov Karaganda State University Publ., 2014)
There are many theories in the educational process suggesting various methods of teaching sciences in English. This article reveals 5E Instructional Model is unique because it focuses on developing the learners’ knowledge by subsequent teaching and consolidation of knowledge. The model consists of five stages (engagement, exploration, explanation, elaboration, and evaluation). The article contains the table, reviewing recommendations and examples of each stage of this model, that encourage thinking, understanding, exploration, problem solving, collaboration, analysis, observation and prediction.
5Е моделі арқылы нақты ғылым пəндері бойынша сабақтарды жоспарлау
Планирование занятий по естественным дисциплинам посредством модели 5E
Keywords: School Education; Biology Teaching; Classroom Teaching; Classroom Activities; Engagement; Exploration; Explanation; Elaboration; and Evaluation